Analysis of stripline configurations loaded with complementary split ring resonators. Issue 6 (27th March 2013) - Falcone, Francisco; Illescas, Jesús; Jarauta, Eduardo; Estevez, Aritz; Marcotegui, Jose Antonio
Abstract In this article, a stripline planar transmission line loaded with complementary split ring resonators (CSRRs), in order to obtain a frequency selective behavior. Due to the quasi‐static resonance frequency of the CSRR elements, given by the excitation by normal incident E‐field, a rejected frequency band can be observed. Simulation as well as measurement results reveal the possibility to apply this type of configuration for the implementation of devices in stripline technology. © 2013 Wiley Periodicals, Inc. Microwave Opt Technol Lett 55:1250–1254, 2013; View this article online at wileyonlinelibrary.com. DOI 10.1002/mop.27569